A multivariate synthetic control chart for monitoring the process mean vector of skewed populations using weighted standard deviations - Khoo, Michael B. C.; Atta, Abdu; Wu, Zhang (Taylor & Francis Group, 2009)
This article proposes a multivariate synthetic control chart for skewed populations based on the weighted standard deviation method.The proposed chart incorporates the weighted standard deviation method into the standard multivariate synthetic control chart.The standard multivariate synthetic chart consists of the Hotelling's T 2 chart and the conforming run length chart.The weighted standard deviation method adjusts the variance–covariance matrix of the quality characteristics and approximates the probability density function using several multivariate normal distributions. The proposed chart reduces to the standard multivariate synthetic chart when the underlying distribution is symmetric.In general, the simulation results show that the proposed chart performs better than the existing multivariate charts for skewed populations and the standard T 2 chart, in terms of false alarm rates as well as moderate and large mean shift detection rates based on the various degrees of skewnesses.